INOVASI DESAIN DAN SIMULASI MODEL PROSTESIS BAWAH LUTUT DENGAN AJUSTABLE SHANK BERBASIS ULIR - Donny Suryawan; Muhammad N Ramadhan; Santo A Dhewanto (Fakultas Teknik - Universitas Riau, 2022)
The number of disabled people in Indonesia is increasing every year from the total population. Data from the Indonesian Ministry of Health in 2014 showed that more than 2.4 million people have little difficulty walking and/or climb stairs. It is including of more than 600 thousand people that having more difficulty. The use of prostheses is the solution to solve that problem. But the development of prostheses in Indonesia is still very little especially below-knee prostheses. The large variety of sizes and heights of disabilities people cause the prosthesis below the knee cannot be mass-produced. So, prosthetic development that can accommodate the anthropometric range of the Indonesian body is necessary. One of the solutions is the development of a below-knee prosthetic with screw-based adjustable shanks. The system allows changes in the height of the prosthesis with increments of 1.5 mm. The simulation of the design shows that the screw-based shank can withstand 2000N loads. Moreover, the making of models that have done is shows that the design has a manufacturing capability.